Decreasing spatial variability of drought in southwest China during 1959–2013 - Meixian Liu; Xianli Xu; Alexander Y. Sun; Kelin Wang (International Journal of Climatology, 2017)
Southwest ( SW ) China is a drought prone region. Knowledge of the risks and coupling characteristics of drought duration and severity is essential for hazards mitigation and water management. Based on probability distributions, copulas, Mann–Kendall test, overlapping moving windows approach and the self‐calibrated Palmer Drought Severity Index ( PDSI ) at 69 stations (1959–2013), this study focused on the trends and spatial variability ( SV ) of (joint) probability drought duration and severity in SW China, and further investigated the potential contributors by analysing the behaviours of precipitation (P), temperature (T), relative humidity ( RH ), wind speed ( WS ), atmospheric moisture flux ( MF ) and divergence ( MFD ). In particular, the SV was represented by the standard deviation, the drought duration and severity were characterized by the number of months with PDSI DM )] and the absolute mean PDSI in drought months ( DS ), respectively. Results showed that, the DM , DS , DM 5 , DS 5 (5‐year return levels for DM and DS ) increased by 0.058 month year −2 , 0.012 month −1 year −1 , 0.039 month year −2 , and 0.009 month −1 year −1 , respectively, and the joint return period T ( DM > 4, DS > 2) decreased by −0.20 year year −1 . Furthermore, due to the decreasing SV in P, T, RH , WS , MF , and MFD , SV of DM 5 , DS 5 and T ( DM > 4, DS > 2) significantly decreased in the past decades, by −0.003 month year −2 , −0.006 month −1 year −1 and −0.03 year year −1 , respectively. These results indicated that drought risks and severity increased significantly in the past decades over SW China. Most importantly, the decreasing SV implied that drought risks and severity might have become more homogeneous in this region. In other words, droughts became more widely spread throughout SW China in the past decades. Therefore, water agencies and governments should be more proactive in seeking measures to improve water resources management and drought mitigation in this region.